PERANCANGAN SISTEM INFORMASI LABORATORIUM FISIKA (SILABFIS) BERBASIS WEB MENGGUNAKAN PROGRAM PHP DAN MYQSL - Widyastuti Widyastuti (UIN Sunan Kalijaga Yogyakarta, 2019)
Laboratory as a center of learning and research activities for both students and lecturers to produce innovations and scientific works that can provide benefits for the development of science, technology, and meeting the needs of the community. Recording and administration using manual records in Microsoft Excel and manual books that are considered ineffective, information about laboratories and administrative services has not been conveyed in general, both students, lecturers and communities outside the campus become a problem that must be resolved in order to improve laboratory services. This study uses the research and development (R & D) method. The development model used is the waterfall software development model. The results of this study are an application of a web-based physics laboratory information system (SILABFIS) that can be accessed online. SILABFIS has a home menu that contains news, information about the laboratory, information on laboratory managers, information on laboratory equipment and materials, laboratory room usage schedules, and modules, standart operational procedure and admin menus that contain administrative and reporting services. The alpha testing test results show that all functions run successfully, meaning that the information system created can already be used.